TANAMAN HUTAN YANG LESTARI: UPAYA MENGANTISIPASI PERUBAHAN IKLIM - Hidayat, Herman (Masyarakat Indonesia, 2012)
This article discusses the rule of plantation forestry, which is only for forest conservation but also for providing raw material for wood industries. It argues that there is a need for emphasizing sustainable forest management based on economic, social and ecological feasibility. Managing forests in sustainable ways can both improve living standard and reduce greenhouse gases. The plantation forestry can support economic development by creating more jobs, and improving social-economic life in rural areas. This paper also discusses the concept of ‘political ecology’, which emphasizes stakeholders’ participation as the key actor for developing plantation forestry. In this concept, the role of government is crucial to provide ‘economic incentives’ for private sectors and local communities, e.g. improved access to banking credit, tax reduction on heavy equipments for pulp and paper industries, and improved infrastructure, such as port and roads. In line with these economic incentives, there is still a need for improving the cooperation between private sector and local community to manage plantation forestry. This type of cooperation will in turn improve governance, forest productivity, innovation, and efﬁ ciency of area utilization.